MÉTODO FONÉTICO EN EL PROCESO DE LECTOESCRITURA EN LOS ESTUDIANTES DE SEGUNDO AÑO DE EGB. - PAREDES VITE PAOLA NALLELY (2024)
The phonetic method for the development of literacy is essential, because it focuses on the recognition and understanding of the sounds that make up words, allowing students to acquire skills necessary to read and write, implying the academic development conducive to other areas of study. Therefore, the objective of this study was to determine the contribution of the phonetic method in the process of teaching literacy in the second year students of EGB of the school "Prof. Cesar Ernesto Medina Salinas" of Baba canton, in the school year 2023-2024. For this, a mixed research methodology was used, with a field and bibliographic design, exploratory and descriptive level, where the applied techniques were observation and survey, through the instruments checklist and questionnaire questions. The results showed that the phonetic method has a high contribution to the development of skills in understanding, oral and written expression, since students have acquired or are in the process of these skills, however, it requires the use of more significant resources, dynamic and motivating, where collaborative work between teachers and parents of families is strengthened.